Estudo comparativo das representações sociais sobre diabetes mellitus e pé diabético - Mantovani, Alessandra Madia; Fregonesi, Cristina Elena Prado Teles [UNESP]; Pelai, Elisa Bizetti [UNESP]; Mantovani, Aline Madia [UNESP]; Savian, Nathalia Ulices [UNESP]; Pagotto, Priscila [UNESP] (Escola Nacional de Saúde Pública Sergio Arouca, Fundação Oswaldo Cruz, 2013)
The study aimed to investigate social representations of the terms diabetes and diabetic foot in different populations. Participants were divided into groups: diabetics (GD); non- diabetics (GN); and non-diabetic healthcare professionals (GP). Personal data were collected, and subjects answered two questions that were expected to evoke five words that came to mind when they thought of diabetes and then diabetic foot. The evoked material was analyzed with the software Ensemble de Programmes Permettant l'Analyse dês Èvocations. A total of 161 subjects participated, including GD (n = 72) with a mean age of 56.12 ± 5.49 years; GN (n = 38) with a mean age of 54.29 ± 7.91 years; and GP (n = 51) with 34.95 ± 7.52 years. The term diabetes evoked 297 words in GD, 172 in GN, and 235 words in GP. The term diabetic foot evoked 180 words in GD, 90 in GN, and 236 in GP. The groups proved to be anxious for more information, thus confirming the need for awareness-raising and educational programs on diabetes, covering comprehensive issues concerning the disease.

O estudo objetivou investigar a representação social dos termos diabetes e pé diabético em diferentes populações. Os participantes foram divididos em grupos: diabético (GD); não-diabético (GN); e profissional da área da saúde nãodiabético (GP). Foram coletados os dados pessoais e os sujeitos responderam a duas perguntas nas quais deveriam evocar cinco palavras que viessem à mente quando pensassem em diabetes e, depois, em pé diabético. O material evocado foi analisado pelo software Ensemble de Programmes Permettant l'Analyse dês Èvocations. Participaram 161 sujeitos, sendo GD (n = 72) com idade média de 56,12 ± 5,49 anos; GN (n = 38) com 54,29 ± 7,91 anos; e GP (n = 51) com idades de 34,95 ± 7,52 anos. Para a representação social do termo diabetes foram evocadas 297 palavras no GD, 172 no GN e 235 palavras no GP. Para o termo pé diabético foram evocadas 180 palavras no GD, 90 no GN e 236 no GP. Os grupos mostraram-se sedentos por maiores informações, confirmando a necessidade de programas de conscientização e educação em diabetes, que contemplem questões globalizantes acerca da doença.

Se realizó un estudio para investigar la representación social de los términos diabetes y pie diabético en diferentes poblaciones. Los participantes fueron divididos en grupos: diabéticos (GD), no diabéticos (GN), y profesional de la salud no diabéticos (GP). Se recogieron datos de carácter personal y los sujetos respondieron a dos preguntas en las que cinco evocan las palabras que vienen a la mente cuando se piensa en diabetes y luego en pie diabético. El material se analizó mediante software Ensemble de Programmes Permettant l'Analyse dês Èvocations. Participaron 161 sujetos con GD (n = 72) con una edad media de 56,12 ± 5,49 años, GN (n = 38) con 54,29 ± 7,91 años y GP (n = 51) de 34 años 95 ± 7,52 años. Para la representación social del término diabetes se evocaron en GD 297 palabras, 172 y 235 en el GP GN. Pie diabético se mencionó en los GD 180 palabras, 90 y 236 en el GP GN. Los grupos solicitaban más información, lo que confirma la necesidad de programas de sensibilización y educación sobre la diabetes, que tienen preguntas sobre la globalización de la enfermedad.
Estudio comparativo de las representaciones sociales sobre diabetes mellitus y pie diabético
A comparative study of social representations of diabetes mellitus and diabetic foot
Keywords: Diabetes Mellitus; Pé Diabético; Humanização da Assistência; Diabetes Mellitus; Diabetic Foot; Humanization of Assistance